PENGARUH PENGGUNAAN MEDIA POWER POINT TERHADAP HASIL BELAJAR SISWA DI SMAN 1 SUNGAI RAYA - Defiani, Ica Kurnia; Utomo, Bambang Budi; Rosyid, Rum (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this research is to find out the effect of using power point media towards students’ academic achievement at the civic education lesson to X IPA 3 in SMA 1 Sungai Raya. The method of this research is an experiment with the form of Pre Experimental Design research with the One Group Pretest Posttest research design. The subject of this research is class X IPA 3 Sungai Raya 1 State High School which has 32 students in the 2017/2018 school year. The research instrument used was 30 questions. Based on the results of the study, the average pre-test results were 75.18 and the average post-test results were 78.28 in the Asymp.sig (2-tailed) normality test the data distribution obtained was greater than alpha 0.05. It can be concluded that Asymp.Sig (2.tailed) in each variable is normally distributed. the amount of t count is 1.340 and the table value is df 62 at the 5% significance level of 1.998. Value of t count> t table (1,340> 1,998), or sig (2-tailed) value of 0,01 smaller than 0,05 so Ho is rejected and Ha is accepted. Based on the calculation of effect size (ES) obtained 0.42 (medium criteria). This means that the use of power point media has a sufficient influence on the learning result of ten grade students in IPA 3 of SMA 1 Sungai Raya. Keywords: The Effect, Power Point Media, Student Academic